The inferring predisposed factors for graduate agropreneur in Malaysia: mismatch? - Lim, Hock Eam; Ahmad, Siti Aznor; Soon, Jan Jan (2015)
Statistics have revealed that the number of graduate entrepreneur especially in agriculture sector is still far below what has been targeted despite the various efforts taken by the Malaysian government. This warrants a study to identify the predisposed factors for graduate agropreneur. Using a sample of 22 established agropreneurs, this paper identifies 28 predisposed factors. The individual level or self-fulfillment factors, interest and satisfaction being entrepreneur, are ranked the most important. The social network and soft skills (creativity and innovation, problem solving) are also ranked among the top. On the other hand, the institutional factors such as degree of entrepreneur is ranked bottom. This finding suggests that the individual level factors are the most important predisposed factors, and it can be complemented by the social and institutional level factors. Using a sample of fresh graduates, it is found that there is a substantial amount of graduates who intended to be entrepreneur. However, it is only a handful them who actually become entrepreneur. Results also reveal that there are around one third of salaries graduates and around half of unemployed (or economically inactive graduates) are intended to be entrepreneur. Thus, government is able to increase the number of graduate agropreneur by facilitating or smoothing the realization of this intention. There is a substantial mis-match between predisposed factors identified by established agropreneur and by the fresh graduates (including those who have become entrepreneur).This implies that the fresh graduate is not having a good understanding on the predisposed factors that enable them to be a successful entrepreneur.